Effect of Bio_fertilizers on Growth and Medicinal active compounds Content of Olive Transplants - Sabah Q. Hamza; Falah H. Radi (University of Thi-Qar Journal of agricultural research, 2021)
A study was carried out in central nursery in Kut affiliated to Wasit Agriculture Directorate on 18/09/2020 to study effect of adding Azotobacter chroococcum and Bacillus megatherium on growth, leaf mineral content and medicinal compounds of “Qaisi” olive transplants. This experiment was carried out on 81 olive transplants with homogeneous vegetative growth as much as possible. Two factors were used in experiment; first factor is addition Azotobacter chroococcum bacteria (A) with three levels: no addition (A0), addition of 30 ml.pot-1 (A30) and addition of 60 ml.pot-1 (A60) and second factor is three levels of Bacillus megatherium (P) is without addition (P0), adding 30 ml.pot-1 (P30) and adding 60 ml.pot-1 (P60).Treatments were replicated three times (three transplants in experimental unit) at factorial experiment in a RCBD. experimental results showed; adding Azotobacter chroococcum to soil at 60 ml.pot-1 (A60) significantly increased in transplant height of 5.78 cm, highest leaf area of 8.99 cm2, highest Branches number of 10.67 branches transplant-1, highest Leaves Carbohydrates content of 4.54 %, highest leaf Caffeic acid content of 14.63 mg.g-1 and highest leaf Vanillic Acid content of 16.90 mg.g-1, also results shows that adding Bacillus megatherium to soil at 60 ml.pot-1 (P60) gave highest increased in transplant height of 5.64 cm, highest leaf area of 8.84 cm2, highest Branches number of 9.78 branches transplant-1, highest Leaves Carbohydrates content content of 4.62 %, highest leaf Caffeic acid content of 15.59 mg.g-1 and highest leaf Vanillic Acid content of 17.89 mg.g-1,